Health education practices of nursing professionals for the self-care of patients with colostomy: scoping review (Research, Society and Development, 2020)
The objective of this scoping review is to map the scientific evidence on health education practices used by nursing professionals to promote self-care in patients with colostomy.: This is a scope review based on the methodological guidelines of the Joanna Briggs Institute, where it sought to answer the following research question: what health education practices developed and used by nursing professionals for the self-care of patients with colostomy? We sought articles that explicitly addressed the mnemonic elements of the study: Population - colostomized patients, Concept - health education practices of nursing professionals for the self-care of patients with colostomy and Context - hospital, home, primary care. The search strategies allowed 509 sources of evidence to be recovered, of which 373 were removed because they corresponded to duplicate records and kept 136 for analysis. Since 110 full articles were not included in the inclusion criteria, 8 studies were left to be included in this research. Concludes in order to support the nurse, educational technologies are allies in order to make the moment of guidance on self-care with ostomy easier and more pleasant, minimizing the impact of the large amount of information to be given. It is concluded that the resources to carry out health education are entering more and more into nursing, thus contributing to the promotion of self-care, adding value to patients and providing an improvement in the quality of life of those who depend on a collection bag.